2012
DOI: 10.1097/id.0b013e3182563ce5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Coated Carbonate Apatite Derived From Avian Eggshell for Potential Use as Bone Substitute. Part I

Abstract: The present research demonstrated the efficient use of microwave in the conversion of natural CaCO3 into CHA with zinc coating. The examined properties showed the potential use of the new material as an antibacterial bone substitute in oral surgery. The trial animal study implied favorable osteoconductive ability of carbonate apatite in new bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…6,15,16 Nano-hydroxyapatite synthesized from eggshell biowaste showed promising results in vitro. 6,1517 Clinical studies have used nano-HA derived from eggshell waste as a graft substitute in apicectomy and extraction defects successfully. 1821…”
Section: Introductionmentioning
confidence: 99%
“…6,15,16 Nano-hydroxyapatite synthesized from eggshell biowaste showed promising results in vitro. 6,1517 Clinical studies have used nano-HA derived from eggshell waste as a graft substitute in apicectomy and extraction defects successfully. 1821…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of mineralizing peri-implant tissue, it is proposed that, presence of Zn in association with P could be linked to three parallel or serially occurring scenarios: 1) biomineralization through pyrophosphate (PPi) and phosphate (Pi) (PPi-Pi) axis [36] that is facilitated by tissue nonspecific alkaline phosphatase whose function is permitted by Zn; 2) inflammation-mediated wound healing pathway through matrix metalloproteinases whose function also is mediated by Zn [37]; 3) presence of osteogenic cells with expression of zinc-finger proteins such as osterix [38]. Of the three elements localized in this study, Zn in particular, has been demonstrated to be an osteoconductive element [39][40][41][42]. Its presence is likely under osteoinductive conditions, mechanical loads included.…”
Section: Discussionmentioning
confidence: 99%
“…Upcoming studies may use other processing methods of the eggshell, like surface-modified carbonated apatite [36,37], eggshell microparticle (ESP) reinforced gelatin-based hydrogels [38], or eggshells from other sources like ostriches [39]. Another possibility would be to combine eggshells and bioactive materials such as recombinant human bone morphogenetic protein-2 (rhBMP-2), as it was done in other recent studies [40,41].…”
Section: Wwwbjbmsorgmentioning
confidence: 99%